2000
DOI: 10.1097/00000374-200008000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Tissue Polypeptide Specific Antigen (TPS) in Alcoholics: A Possible Marker of Alcoholic Hepatitis

Abstract: Serum TPS is frequently increased in alcoholics and may be a marker of alcoholic hepatitis. Specificity of this molecule as a tumor marker is limited in alcoholics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 18 publications
3
19
0
Order By: Relevance
“…Several groups previously reported elevated circulating levels of CK‐18 fragments in patients with excessive alcohol consumption. Some authors found high tissue‐polypeptide–specific antigen, a CK‐18 epitope, in the serum of patients with active alcohol consumption, including some with proven AH . Other groups observed high circulating levels of M65 and M30 epitopes in patients with alcoholic liver disease and advanced fibrosis and in patients with clinically presumed AH but without histological assessment .…”
Section: Discussionmentioning
confidence: 99%
“…Several groups previously reported elevated circulating levels of CK‐18 fragments in patients with excessive alcohol consumption. Some authors found high tissue‐polypeptide–specific antigen, a CK‐18 epitope, in the serum of patients with active alcohol consumption, including some with proven AH . Other groups observed high circulating levels of M65 and M30 epitopes in patients with alcoholic liver disease and advanced fibrosis and in patients with clinically presumed AH but without histological assessment .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this shows some consistency with prior studies that have documented an increased peripheral pro‐inflammatory state via changes in similar cytokine markers, within alcohol‐dependent individuals. For example, attenuated levels of the anti‐inflammatory IL‐10 have been observed following early abstinence in cocaine‐dependent individuals (Fox et al., ), alcoholics free of liver pathology (Gonzalez‐Quintela et al., ), and abstinent alcoholics without anxiety and/or mood disorders (Fox et al., 2010b). Of note, IL‐10 levels were not obtained in the current study of nondependent social and problem drinkers and should be examined in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with AH had a history of chronic alcohol intake of at least 80 g/d (immediately prior to their admission at the hospital, the average alcohol intake reported by the patients was as high as 400 g/d) with clinical and biochemical features of AH, including increased serum levels of (i) aspartate aminotransferase (AST) (range: >1.5 times the normal values to <300 IU/l), (ii) AST/alanine aminotransferase (ALT) ratio (>2), (iii) γ‐glutamyl transpeptidase values, and (iv) bilirubin (≥2 mg/dl, n = 20) (Amini and Runyon, ; Dunn et al., ) or keratin‐18 concentrations (>3‐fold, n = 5) (Gonzalez‐Quintela et al., ). All patients had mild to moderate AH, as determined by the Maddrey's discriminant function—[4.6 × (patient's prothrombin time − control prothrombin time, expressed in seconds)] + serum bilirubin level, in milligrams per deciliter—consistently lower than 32.…”
Section: Methodsmentioning
confidence: 99%